Literature Survey on Islamic Microfinance - Nik Nur Izzati Nik Muhammad Azmi; Mohamed Asmy Bin Mohd Thas Thaker (Global Review of Islamic Economics and Business, 2020)
Islamic microfinance can be seen as an emerging industry in some Muslim countries like Indonesia, Malaysia, Pakistan, Bangladesh, and MENA regions. It acts as a movement to eradicate poverty in the society and to help improve the social standard of the poor people. The concept of Islamic microfinance is similar to those implemented in conventional microfinance except for it adheres to several points and concepts which in line with the Shariah rulings. As a growing industry, Islamic microfinance does facing several challenges such as limited outreach in the market, lack of expertise in the industry, governance and management problems, and many more. Hence, this paper will discuss further the issues and challenges faced by Islamic microfinance institutions in selected Muslim countries. Plus, some suggestions are given at the end of this paper to solve these issues.